As práticas do currículo integrado no curso de Direito - Albuquerque, Alessandra Patricia de Souza (2018)
This research has as main objective to understand the professors’ comprehension about the practices of the integrated curriculum at a Law School of a private high education institution, situated in Vitória, estate of Espírito Santo, and its relation with the professors’ education. The specific objectives of this study are to understand the concept of the integrated curriculum and its relation with the professors’ pedagogical education; to understand the relation among the Law of Directives and Bases of National Education (LDBEN), the national curriculum legal policies for Law courses, the Law school’s pedagogical project of the researched high education institution (PPc), and the integrated curriculum developed by the professors who participated in the study; and, to understand the relation between the methods of teaching in a Law school at the researched high education institution and its pedagogical project. A qualitative method procedure was used on this research, as an exploratory study, including interviews with five professors of the Law course of the high education institution. The results presented the respondents’ comprehension about the practices of the integrated curriculum and its relation with their pedagogical education and also indicated that the practices of the integrated curriculum include a larger educational project conceived to promote a wider vision of the Law; that practicing the integrated curriculum requires pedagogical education and there is still resistance to pedagogical continuous training by the professors of the high education institutions; that there is a relation between the professors’ education and the practices of the integrated curriculum at the Law school of the researched institution, as well as there is a relation between those practices and the Law school’s pedagogical project; that the interviewed professors do not face teaching as a secondary professional career; that sharing experiences with other colleagues contributes to the professors’ pedagogical development. The results showed that there is a direct and consistent relation among the LDBEN, the national curriculum legal policies of the Law courses, the PPc, and the integrated curriculum developed by the professors who participated in the study. The research considers the need to value teaching training by means of public policies and/or through institutional initiatives in order to promoting pedagogical continuous training to its own professors.